Pemetaan Daerah Krisis Sinyal Untuk Peningkatan Telekomunikasi Di Indonesia Berbasis GIS - Syahrul Adrianto; Bambang Agus Herlambang (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Telecomunications plays in important role in everyday life, and signal crisis is a major challenge in many parts of Indonesia. This study aims to create a detailed map of areas effected by the signal and internet traffic crisis using a Geographic Information System (GIS) based approach. The study includes data collection of communication signals and their determinations from various regions, providing a comprehensive picture of the network situation in Indonesia. A GIS analysis approach was used to create a map of the distribution of signal crisis areas, allowing the identification of spatial patterns that may be the root cause of this problem. The study focused on the geographical structure, signal interference and mobile internet data usage in each household as factors to consider when investigating the causal factors. The results show that there is a significant relationship between certain factors and crisis signaling. An in-depth understanding of the spatial data and causes of the signaling crisis is the basis for developing more effective improvement strategies. The practical implications of this study include recommendations for improved telecommunications infrastructure and better mitigation strategies. Therefore, this study not only presents the problem but also provides detailed insights to guide policies and measures needed to improve the quality of telecommunication services in Indonesia.